Teachers’ perspectives on social media in schools in the UAE - Alkutich, Mohamad Ezzat (2018)
Social media plays a fundamental role worldwide in changing the way of communication is carried out. Using social media in schools has its pros and cons. This paper aims explores the perspectives of teachers in Abu Dhabi schools regarding the use of social media for instructional purposes in the classroom. The study investigated recent experience of teachers with social media in schools, as well as explore teachers' point of view regarding the importance of social media in teaching and learning. Finding shows that teachers consider social media is a significant tool in their day-to-day school communication, and there was an appreciation for the use of social media in teaching and learning. Moreover, teachers depicted that the implementation of social media in teaching and learning is still an elusive target.